(untitled) (Research, Society and Development, 2022)
Fires are important sources of damage to forest ecosystems in developing regions. Fires have a relevant impact on the Amazonian ecosystem in the dry season with emissions of atmospheric pollutants. This article aimed to locate the spatial distribution of fire hotspots in the municipality of Acará in the state of Pará during the period from 2009 to 2018. if the Kernel estimator used the thermal band of the AQUA_M-T satellite, handling its data in ten periods. The data discussed indicate that fires constitute an annual phenomenon, as it was present throughout the monitored time interval (2009 to 2018). The fires were observed throughout the region of the municipality of Acará and that the fire outbreaks can be transported for thousands of kilometers.